University Student Responses to the Implementation of the Active Debate Method in the Pancasila Course - Herianto; Marthaliakirana, Angsoka Dwipayana; Abdilah, Hayatining Suci (Universitas Kristen Cipta Wacana, 2025)
This study aims to determine student responses to the implementation of the active debate method in the Pancasila course. This research is quantitative and descriptive in nature. The subjects of this study were 131 students from the Faculty of Teacher Training and Education at Sultan Ageng Tirtayasa University. The instrument used was an online questionnaire employing a Likert scale (1-5). The research procedure involved asking students who had participated in the active debate method during the Pancasila course to complete an online questionnaire. The questionnaire results were analyzed using quantitative descriptive analysis to ascertain student responses to the use of the debate method. The findings indicate that student responses to the active debate method in the Pancasila course fall under the